Multiphysics simulation of an anisothermal reactive spontaneous capillary rise between electric rotor wires - Moisy, Amélie; Comas-Cardona, Sébastien; Désilles, Nicolas; Genevée, Pascal; Kolehmainen, Jere (Frontiers in Materials, 2023)
Introduction: The rotor is the mobile component of an electric motor. A wound rotor is composed primarily of a steel core with insulated copper wires wound around it, after which the winding is immersed into a liquid acrylate-based thermosetting resin bath whose role is to ensure the performance and durability of the motor. This impregnation with resin between the wires occurs under controlled temperature settings to facilitate resin flow and polymerization. This process does not involve any pressurization to further facilitate resin flow between the wires; this suggests that, in addition to viscous effects, capillary and gravity forces play a significant role in the impregnation process. Methods: Our ultimate objective is to evaluate the quality of this impregnation. Doing so requires the characterization and simulation of a multi-material and multiphysics process in which heat transfer, polymerization kinetics, and resin flow are strongly coupled. This paper presents a fully coupled macroscopic multiphysics simulation of a unidirectional thermo-regulated capillary rise set-up. Discussion: The modeling choices made produced a good level of agreement with experimental data and enable explanation of a sudden change of regime observed at 120°C, which can be attributed to the polymerization and thermal gradients and their impact on fluid dynamics.